Chinese herbal medicine anticancer cocktail soup activates immune cells to kill colon cancer cells by regulating the gut microbiota-Th17 axis - Nie, Xiaoli; Geng, Zixiang; Liu, Jianjun; Qi, Li; Wang, Zetian; Liu, Te; Tang, Jianguo (Frontiers in Pharmacology, 2022)
Chinese herbal medicines are effective for treating colon cancer (CC). CC development is reportedly associated with gut microbiota dysbiosis and immune function dysregulation. Herein we explored the therapeutic effects of a Chinese herbal medicine anticancer cocktail soup (CHMACS) on mice with CC and also explored its regulatory effects on gut microbiota. In vivo experiments indicated that CHMACS significantly inhibited the proliferation and tumorigenicity of CC cells. Further, CHMACS treatment decreased the proportion of CD8+ T, natural killer, and Th17 cells. HPLC/MS analysis showed that CHMACS comprised 227 active components. 16S rRNA sequencing revealed, for example, an increase in the relative abundance of uncultured_bacterium_g_Turicibacter and a decrease in that of uncultured_bacterium_g_Coriobacteriaceae_UCG-002 in gut microbiota of CHMACS-treated mice. Microbial diversity cluster analysis revealed that Verrucomicrobia, Spirochaetes, Fusobacteria, Patescibacteria, and Firmicutes contributed the most to fecal microbial diversity. Kyoto Encyclopedia of Genes and Genomes metabolic pathway analysis and clusters of orthologous groups of protein annotation indicated that CHMACS treatment induced amino acid metabolism and suppressed carbohydrate metabolism. Moreover, we found a strong association between changes in metabolites and immune cell maturation and activation. To summarize, our findings suggest that CHMACS kills CC cells by regulating gut microbiota and activating immune cells.